Perceiving Immigrants as a Threat: A Motivational Approach to False Consensus. (December 2022) - Gill, Hyungjin; Rojas, Hernando
False consensus, or biased projection of one's opinion onto others, has repeatedly been described by political communication scholars as a derivative of selective exposure to attitude-consistent information. This study proposes a distinctive approach to understanding the phenomenon by suggesting "perceived threat" as a motivational factor that contributes to self-serving estimates of public opinion. Based on a nationally representative sample of U.S. adults, we test a path model in which political ideology relates to false consensus regarding the issue of immigration through cognitive assessments of communication environment and perceived immigration threat. Results suggest that the relationship between cognition and false consensus may not be direct but instead works through motivational factors when one perceives threat, and that conservatives are more sensitive to outgroup threat and thus are more likely to overestimate public consensus for their attitudes on immigration than their ideological counterparts. Implications of these findings are discussed.